The rise and endurance of radical right movements - Caiani, Manuela (Current sociology, 2019)
This article reviews the scholarship on radical right movements in Europe. It focuses on three strands of this literature: first, the macro-level contextual opportunities-based explanations for the fortunes of these movements; second, internal supply-side approaches, referring to the internal organizational resources – leadership, communication and propaganda – that support the mobilization; and third, the individual (micro-level) factors of the emergence and the rise of radical right movements. The goal is to shed light on all these different approaches to explain the ‘Who’, ‘When’, ‘How’ and ‘Why’ of the emergence and (violent) mobilization of radical right groups, using empirical evidence drawn from various case studies in Western, Eastern and Central Europe. This is a topic often neglected in the academic literature on the radical right, which still focuses mainly on political parties and elections. The article concludes by discussing possible future directions for radical right movement research, including the transnationalization of the radical right, the usage of the Internet and radical right ‘movement parties’.